The Relationship Between Protein, Iron, Folic Acid, Vitamin C Intake and Breakfast Habits With The Incidence of Anemia in Female Students of SMPN 152 Jakarta - Anggraini, Vani Rizkia; Maulida, Nursyifa Rahma; Aini, Rahmatika Nur (Ikatan Sarjana Gizi Indonesia (ISAGI), 2024)
Anemia is a condition where the number of red blood cells or the level of hemoglobin is lower than normal. In Indonesia, the prevalence of anemia among adolescent girls remains quite high at 32%. Inadequate nutrient intake can disrupt red blood cell formation, particularly important nutrients such as protein, iron, vitamin C, and folic acid. This study aims to investigate the relationship between the intake of protein, iron, folic acid, vitamin C, and breakfast habits with the incidence of anemia among female adolescents in junior high school. This is a quantitative study with a cross-sectional design, analyzed using Spearman correlation tests, conducted at SMPN 152 Jakarta with a sample size of 50 individuals. Data on protein, iron, folic acid, and vitamin C intake were obtained through 24-hour food recall interviews, breakfast habits were assessed via a questionnaire, and anemia data were collected through blood samples using a digital Hb checker. The analysis results indicate a relationship between protein intake (p = 0.000), iron intake (p = 0.000), folic acid intake (p = 0.030), vitamin C intake (p = 0.010) and the incidence of anemia, while no relationship was found between breakfast habits (p = 0.161) and anemia incidence. It is concluded that there is a correlation between protein intake, iron intake, folic acid intake, and vitamin C intake with anemia incidence at SMPN 152 Jakarta. The variable most strongly correlated with anemia incidence is iron intake with a value of (r = 0.640).